30. SATISFACTION OF PATIENTS AND THEIR FAMILY FOR OUTPATIENTS SERVICES AT DUC GIANG GENERAL HOSPITAL IN 2019 (Vietnam Journal of Community Medicine, 2023)
Objectives: (1) Determine the satisfaction level of patients and their family members with outpatient medical services at Duc Giang General Hospital in 2019; (2) Identify a number of factors affecting the satisfaction of patients and their family members with outpatient medical examination and treatment services and propose intervention solutions.Subjects: As a patient, the patient’s family members came for examination and treatment at Duc Giang General Hospital in 2019, excluding patients who are not eligible for subclinical indications and patients who are in an emergency or are about to be transferred.Result: Among the 438 patients interviewed, the majority of patients interviewed were insured (in and out of network a), accounting for 94%. The target group of hospital fees accounts for only a small part of 6%. This difference was statistically significant with p < 0.05. In terms of patient satisfaction, the satisfaction level of patients and their family members with the hospital’s services was assessed as satisfied, with an average of 4.28/5. The use and experience of different services was the most appreciated in the level of behavior, professional capacity of medical staff as well as service delivery results with an average rating of 4. ,4/5. However, the transparency of information and procedures for treatment and treatment reached the lowest level compared to the average of other services, with an average score of 4.1/5.Conclusion: The majority of outpatients feel satisfied and very satisfied with the corresponding rate of 63,22% : 30,81% and the overall average satisfaction level in all aspects is above 4.
Keywords: Satisfaction; outpatients services.